2012
DOI: 10.1245/s10434-012-2554-5
|View full text |Cite
|
Sign up to set email alerts
|

The Unique Clinical Characteristics of Melanoma Diagnosed in Children

Abstract: Background Studies have demonstrated a higher rate of nodal metastases in melanoma of childhood, but there is controversy about the overall prognosis relative to adults. We describe a large single-institution experience with pediatric melanoma and assess prognostic characteristics. Methods Retrospective review identified 126 patients diagnosed with melanoma at <21 years of age and referred for treatment from 1986 to 2011. Atypical lesions were excluded. Clinicopathologic characteristics were correlated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 71 publications
(44 citation statements)
references
References 28 publications
0
43
0
1
Order By: Relevance
“…Despite the limited number of patients in this preliminary study, the following conclusions can be drawn: (i) in some SNi, as in the cases of ASNi, the follow-up remains the most important factor to determine the clinical behavior; (ii) FISH seems reliable in most of the lesions found in adults, although not superior to conventional histology; (iii) FISH assay in pediatric patients with SNi should be interpreted carefully in the context of the histological features as melanomas in the pediatric population show distinct chromosomal aberrations [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the limited number of patients in this preliminary study, the following conclusions can be drawn: (i) in some SNi, as in the cases of ASNi, the follow-up remains the most important factor to determine the clinical behavior; (ii) FISH seems reliable in most of the lesions found in adults, although not superior to conventional histology; (iii) FISH assay in pediatric patients with SNi should be interpreted carefully in the context of the histological features as melanomas in the pediatric population show distinct chromosomal aberrations [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that compared with adults, pediatric melanoma patients exhibit higher rates of lymph node metastases ranging from 25 to 40% [10]. Although higher rates of lymph node metastases have been reported in pediatric melanoma patients, the prognostic value of sentinel lymph node biopsy (SLNB) has not been extensively studied in this population.…”
Section: Discussionmentioning
confidence: 99%
“…Although higher rates of lymph node metastases have been reported in pediatric melanoma patients, the prognostic value of sentinel lymph node biopsy (SLNB) has not been extensively studied in this population. The few studies on SLNB for pediatric melanoma have reported varying results, with some studies reporting no recurrences or deaths in positive SLNB patients while one study showed that the overall survival rate of 94% seen in pediatric melanoma patients dropped to 79 % in positive SLNB patients [10,11]. Currently, there is a common agreement that pediatric patients with clinically localized melanomas >1 mm thickness should be offered SLNB.…”
Section: Discussionmentioning
confidence: 99%
“…48,49 The rate of sentinel node involvement in pediatric melanoma is well established to be higher than that in adult melanoma, roughly 25% to 40%. 5052 Data regarding sentinel node status in AMPs are difficult to interpret, because most reports are retrospective reviews and likely have recategorized some AMPs with obvious malignancy in the nodes as melanoma.…”
Section: Staging Evaluations In Pediatric Patients With Ampmentioning
confidence: 99%